Pengaruh modernisasi sistem administrasi, sosialisasi dan pemeriksaan pajak terhadap kepatuhan WPOP - Yulkhaq , Muhammad Yoga Fatahillah; Africa, Laely Aghe (Journal of Accounting and Digital Finance, 2024)
Taxes are the result of levies that must be paid by the community, especially taxpayers, for the common welfare and are the main source for the state in preparing the State Revenue and Expenditure Budget (APBN). It is hoped that state revenues through tax revenues will be able to improve state infrastructure and society's welfare. This research aims to examine the influence of modernization of the tax administration system, tax socialization, and tax audits on taxpayer compliance. The data collection method in this research was a questionnaire distributed via a Google Form link. The number of respondents from this research was 96 who had an NPWP and were domiciled in Sidoarjo. The data analysis technique uses multiple linear regression analysis. This research indicates that modernization of the tax administration system affects individual taxpayer compliance. Tax socialization does not affect individual taxpayer compliance. Tax audits affect individual taxpayer compliance.